Analysis of Marketing Strategy in Optimizing New Student Registration at the University of Muhammadiyah Sukabumi - Prianugraha, Alreza; Deni Muhammad Danial, R; H. Suwiryo, Darmo (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
The purpose of this study is to identify and analyze the general marketing strategy used to attract prospective new students of the University of Muhammadiyah Sukabumi (UMMI). Data was collected through observation, document analysis, and interviews. This study uses a descriptive method with a qualitative approach and applies Miles & Huberman's qualitative analysis to process the data. The results of the study show that the use of marketing mix dimensions (products, costs, places, promotions) by UMMI in optimizing the number of new student enrollment has resulted in several alternative strategies, including efforts to improve promotional strategies such as communicating advantages through hard selling, building an image through soft selling, and expand the reach of promotion and increase credibility through cooperative relationships with government agencies and other universities. Supporting factors include human resources, the existence of a scholarship system, and financial aid to provide opportunities for prospective students from diverse financial backgrounds to gain access to higher education. Adequate facilities and infrastructure, such as modern laboratories and a complete library, while the inhibiting factor is stiff competition with other universities offering similar programs and limited marketing budgets can also develop effective and extensive marketing campaigns.